Patent protection and threat of litigation in oligopoly - Carlo Capuano; Iacopo Grassi (Economics and Econometrics Research Institute (EERI), 2018)
In recent years, the increasing awarding of patents has captured the attention of scholars operating in different fields. Economic literature has studied the causes of this proliferation; we propose an entry game focusing on one of the consequences, showing how an incumbent may create a patent portfolio in order to control market entry and to collude. The incumbent fixes the level of patent protection and the threat of denunciation reduces the entrant's expected profits; moreover, if the entrant deviates from collusion, the incumbent can strengthen punishment suing the competitor for patent infringement, reducing her incentive to deviate. Our analysis suggests that antitrust authorities should pay attention to the level of patent protection implemented by the incumbent and note whether the holder of a patent reacts to entry by either suing or not suing the competitor. In the model, we use completely general functional forms in analyzing the is- sues, and this allows us to obtain general results not depending on the assumptions about the kind of oligopolistic competition.
Keywords: D43; K21; L13; 330; patents; patent portfolio; litigation; collusion; foreclosing; entry game